2019
DOI: 10.1038/s41557-019-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

N-heterocyclic carbene-functionalized magic-number gold nanoclusters

Abstract: Magic number metal nanoclusters are atomically precise nanomaterials that have enabled unprecedented insight into structure-property relationships in nanoscience. Thiolates are the most common ligand, binding to the cluster via a staple motif in which only central gold atoms are in the metallic state. The lack of other strongly-bound ligands for nanoclusters with different bonding modes has been a significant limitation in the field. Herein, we report a previously unknown ligand for gold (0) nanoclusters: N-he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
360
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 405 publications
(382 citation statements)
references
References 52 publications
17
360
3
2
Order By: Relevance
“…Forc omparison, this value is slightly larger than that in i Pr 2 -bimyAuBr (1.978 (8) ), [15] but somewhat less than that in [Au 11 (PPh 3 ) 7 ( i Pr-bimy)Cl 2 ]Cl (2.09 (2) ). [14] Interestingly,s tructure of 1 quite resembles that of Au 25 , [16] or Pt 2 Ag 23 protected by tertiary phosphines, [17] indicating that in shaping structure of nanoclusters,NHCs can adopt similar binding modes with tertiary phosphines.T he similar observation has also been revealed in organometallic complexes.C luster 1 is also closely related to the series of vertex-sharing biicosahedral bimetallic (AuÀAg) and trimetallic (Au-Ag-M where M = Ni, Pd, Pt) clusters stabilized by phosphine and halide ligands reported by Teoand co-workers as early as the 1980s. [18] Thec omposition of 1 was confirmed by ESI-MS under positive ion mode in CH 2 Cl 2 .Asshown in Figure 2a,the ESI-MS spectrum revealed only as ingle peak at 3756 m/z, corresponding to [Au 25 ( i Pr 2 -bimy) 10 Br 7 ] 2+ .P erfect agreement was observed between the experimental spectrum and simulated isotopic distribution pattern.…”
Section: Synthesis and Atomic Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Forc omparison, this value is slightly larger than that in i Pr 2 -bimyAuBr (1.978 (8) ), [15] but somewhat less than that in [Au 11 (PPh 3 ) 7 ( i Pr-bimy)Cl 2 ]Cl (2.09 (2) ). [14] Interestingly,s tructure of 1 quite resembles that of Au 25 , [16] or Pt 2 Ag 23 protected by tertiary phosphines, [17] indicating that in shaping structure of nanoclusters,NHCs can adopt similar binding modes with tertiary phosphines.T he similar observation has also been revealed in organometallic complexes.C luster 1 is also closely related to the series of vertex-sharing biicosahedral bimetallic (AuÀAg) and trimetallic (Au-Ag-M where M = Ni, Pd, Pt) clusters stabilized by phosphine and halide ligands reported by Teoand co-workers as early as the 1980s. [18] Thec omposition of 1 was confirmed by ESI-MS under positive ion mode in CH 2 Cl 2 .Asshown in Figure 2a,the ESI-MS spectrum revealed only as ingle peak at 3756 m/z, corresponding to [Au 25 ( i Pr 2 -bimy) 10 Br 7 ] 2+ .P erfect agreement was observed between the experimental spectrum and simulated isotopic distribution pattern.…”
Section: Synthesis and Atomic Structurementioning
confidence: 99%
“…[6b] Earlier DFT calculations on am ixed-ligand [Au 11 (PPh 3 ) 7 (NHC i-Pr )Cl 2 ]Cl cluster have shown that the Au-carbene bond can be stronger than Auphosphine bond by up to 0.9 eV.T his explains also the observed superior thermal stability of 1 over 2 in this work. [14] Surface Reactivity and Catalytic Performance While 1 was highly stable in solution, the presence of halides on the cluster motivated us to explore its surface reactivity.T oour surprise,when mixing phenylacetylene (PA) and 1 together,both Fourier transform infrared spectroscopy (FTIR) and 13 CNMR showed that the chemical environment of PA changed significantly (Supporting Information, Figures S14 and S15), indicating that PA can easily bind to the surface of 1.W et hus proposed that 1 would be an ice candidate catalyst for reactions involving the activation of alkynes.H ere we chose the cycloisomerization of alkynyl amines to form indoles as am odel reaction. Indoles are important heterocycles which are broadly used in material science and biology.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore,t hiol-protected Au 25 (SC 2 H 4 Ph) 18 (3) also exhibits much worse stability than that of 1 (Figure 4c and pink curve in Figure 4d). [14] Surface Reactivity and Catalytic Performance While 1 was highly stable in solution, the presence of halides on the cluster motivated us to explore its surface reactivity.T oour surprise,when mixing phenylacetylene (PA) and 1 together,both Fourier transform infrared spectroscopy (FTIR) and 13 CNMR showed that the chemical environment of PA changed significantly (Supporting Information, Figures S14 and S15), indicating that PA can easily bind to the surface of 1.W et hus proposed that 1 would be an ice candidate catalyst for reactions involving the activation of alkynes.H ere we chose the cycloisomerization of alkynyl amines to form indoles as am odel reaction. [14] Surface Reactivity and Catalytic Performance While 1 was highly stable in solution, the presence of halides on the cluster motivated us to explore its surface reactivity.T oour surprise,when mixing phenylacetylene (PA) and 1 together,both Fourier transform infrared spectroscopy (FTIR) and 13 CNMR showed that the chemical environment of PA changed significantly (Supporting Information, Figures S14 and S15), indicating that PA can easily bind to the surface of 1.W et hus proposed that 1 would be an ice candidate catalyst for reactions involving the activation of alkynes.H ere we chose the cycloisomerization of alkynyl amines to form indoles as am odel reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[12] Theoretical work also suggested that NHCs may function as new ligands for Au surface modification and NCs protection. [14] Ther eported [Au 11 (PPh 3 ) 7 ( i Pr-bimy)Cl 2 ] + cluster contains both phosphine and NHC ligands on its surface. [14] Ther eported [Au 11 (PPh 3 ) 7 ( i Pr-bimy)Cl 2 ] + cluster contains both phosphine and NHC ligands on its surface.…”
Section: Introductionmentioning
confidence: 99%